2023
DOI: 10.3390/diagnostics13040813
|View full text |Cite
|
Sign up to set email alerts
|

From Pathogens to Cancer: Are Cancer Cells Evolved Mitochondrial Super Cells?

Abstract: Life is based on a highly specific combination of atoms, metabolism, and genetics which eventually reflects the chemistry of the Universe which is composed of hydrogen, oxygen, nitrogen, sulfur, phosphorus, and carbon. The interaction of atomic, metabolic, and genetic cycles results in the organization and de-organization of chemical information of that which we consider as living entities, including cancer cells. In order to approach the problem of the origin of cancer it is therefore reasonable to start from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Studies have noted that mtDNA mutations, dysregulation of mtDNA, and disturbances in the communication between nuclear DNA and mtDNA may affect cellular health and in turn, predispose to carcinogenesis [ 54 ]. A recent hypothesis also suggested that the mitochondria may under the influence of microbial pathogens can transform themselves into super-power cells or immortal cancer cells that enable tumor formation [ 55 ]. In view of the potential role of mtDNA in aging and diseases including cancers, the role of gene editing in therapeutic management was being explored [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies have noted that mtDNA mutations, dysregulation of mtDNA, and disturbances in the communication between nuclear DNA and mtDNA may affect cellular health and in turn, predispose to carcinogenesis [ 54 ]. A recent hypothesis also suggested that the mitochondria may under the influence of microbial pathogens can transform themselves into super-power cells or immortal cancer cells that enable tumor formation [ 55 ]. In view of the potential role of mtDNA in aging and diseases including cancers, the role of gene editing in therapeutic management was being explored [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…In other words, cancer is clinically caused by the uncontrolled growth of several cells. It may metastasize to other parts of the body (4). There are various cancer treatments, depending on the cancer type and how advanced it is, such as surgery, radiation therapy, chemotherapy, targeted therapy, and precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Some in vitro evidence indicates that another entry factor that potentiates SARS-CoV-2 s infectivity [14] is represented by neuropilin-1 (NRP-1), a signaling protein highly present in the O.C. In addition to the well-known roles played by ACE2 and TMPRSS2, additional endosomal proteases (CTSB, CTSL, and BSG) and tissue-specific proteases (TMPRSS4 and TMPRSS11D) might facilitate the virus s entrance into cells for intracellular reproduction [15,16]. Interaction of the cell membrane-based receptor ACE2 of the host cell with the spike protein of SARS-CoV-2 triggers the endosomal pathway internalization, which results in virus endocytosis [13,17].…”
Section: Introductionmentioning
confidence: 99%